Life Development with the Principles of the Four Foundations of Mindfulness - Somchit, Somchai; Rattanaphan, Phannapha; Khammuangsaen, Boonruam (Journal of Dhamma for Life, 2025)
This academic article aims to 1) study the concept of the Four Foundations of Mindfulness, 2) study and analyze the development of life with the principles of the Four Foundations of Mindfulness, and 3) present the principles of the Four Foundations of Mindfulness for use in life development. Developing life with the principles of the Four Foundations of Mindfulness is an approach that helps create mindfulness and wisdom, leading to a balanced and peaceful life. The Four Foundations of Mindfulness consist of Kayanupassana (mindfulness of the body), Vedananupassana (mindfulness of feelings), Cittaanupassana (mindfulness of the mind), and Dhammaanupassana (mindfulness of dhamma). Practicing mindfulness in each area helps to understand oneself, reduce suffering, and develop the right attitude. Kayanupassana helps us to be more aware and take care of our physical health, improve behaviors that affect health. Vedananupassana helps to manage emotions, reduce distractions, and understand the nature of feelings. Cittaanupassana helps to control thoughts, reduce prejudice, and develop wisdom. Dhammaanupassana helps to understand the truth of life, reduce attachment, and lead to the development of morality. Continuous practice of the Four Foundations of Mindfulness can be applied in daily life. It helps to improve work efficiency, problem solving and building good relationships. Being aware of the present moment can help reduce stress and increase happiness in life sustainably. Therefore, practicing the Four Foundations of Mindfulness is an important guideline for developing oneself to achieve true peace and understanding of life.